Cryopreservation of Rat Seminiferous Tubules Using Biopolymers and Slow Non-Controlled Rate Cooling - Volkova, Nataliia O.; Yukhta, Mariia S.; Chernyshenko, Lyudmyla G.; Stepanyuk, Lyudmyla V.; Sokil, Larisa V.; Goltsev, Anatoliy M. (Problems of Cryobiology and Cryomedicine, 2019)
One of the current trends in biomedical research is the use of novel biological products and cryotechniques to maintain fertility, especially in case of planned cytotoxic therapy. Existing protocols of testicular tissue cryopreservation require further optimization and improvement. This study represents a comparative evaluation of the effect of biopolymers (bovine serum albumin, collagen and fibrin gel) in combination with either 0.6M dimethylsulfoxide or 0.7 M glycerol on morphofunctional characteristics of seminiferous tubules of immature rats after cryopreservation using slow non-controlled cooling down to 70Â°C for 40 min with following immersing the samples into liquid nitrogen. Based on the results of the analysis of viability, total activity of lactate dehydrogenase, MTT-test and histomorphometric data (cell retraction degree, epithelium desquamation frequency, number of cells with condensed nuclues, existingÂ spermatogenic layer deffects), the combination of the fibrin gel with a 0.7 M glycerol has been found to be the most optimal among all the studied combinations of biopolymers and cryoprotectants. The obtained data can be used for substantiation and development of effective cryopreservation methods for human seminiferous tubules using biopolymers. Probl Cryobiol Cryomed 2018; 28(4): 278-292